2023
DOI: 10.1021/acs.energyfuels.3c00908
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Methanation on Ni Catalysts Supported over Activated Carbons Derived from Cork Waste

Filipe Mateus,
Paula Teixeira,
José M. Lopes
et al.

Abstract: Activated carbons (ACs) derived from cork wastes were for the first time used as supports for CO2 methanation catalysts. Cork wastes (natural-N and processed-P) were physically activated under N2/H2O(v) atmosphere at 800 °C to obtain the corresponding AC supports (ACN and ACP, respectively). Ni and Ni-CeO2 catalysts were prepared by loading the ACs with 15 wt % Ni (Ni/AC) or 15 wt % Ni and 15 wt % Ce (NiCe/AC) by incipient wetness impregnation or co-impregnation, respectively, using 2-propanol as the solvent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This transition is likely attributed to the role of the Ni precursor or NiO x species in the etching process of the CAC during the reduction phase. Concurrently, the S micropore BET / S BET value decreases gradually, suggesting that part of the Ni nitrate is converted from Ni δ+ to Ni 0 , thereby etching the micropores of CAC during reduction. In the sulfide catalysts, lower specific surface areas of micropores and micropore volumes are observed compared to their nonsulfide counterparts. This difference can be attributed to the sulfidation process during which the Ni 0 particles transform into bulk Ni 3 S 2 particles.…”
Section: Resultsmentioning
confidence: 99%
“…This transition is likely attributed to the role of the Ni precursor or NiO x species in the etching process of the CAC during the reduction phase. Concurrently, the S micropore BET / S BET value decreases gradually, suggesting that part of the Ni nitrate is converted from Ni δ+ to Ni 0 , thereby etching the micropores of CAC during reduction. In the sulfide catalysts, lower specific surface areas of micropores and micropore volumes are observed compared to their nonsulfide counterparts. This difference can be attributed to the sulfidation process during which the Ni 0 particles transform into bulk Ni 3 S 2 particles.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, among the CO 2 applications, the methanation reaction is simple to conduct under mild temperature conditions (in the 200-500 • C range); more importantly, such a reaction can be accomplished at ambient pressure [17]. These salient features of CO 2 methanation make it highly popular; Figure 1 shows the remarkable increase in publications on CO 2 methanation in the last ten years.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the CO 2 methanation performance of Ni-based catalysts, various strategies have been extensively investigated. These include exploring catalyst preparation methods, introducing a second metal, optimizing supports, , and incorporating promoters. , Among them, CeO 2 as a promoter has aroused significant interest owing to its abundant oxygen vacancy, which could facilitate CO 2 conversion . Liu et al prepared Ni-CeO 2 /Al 2 O 3 catalysts using the co-impregnation method and observed that the addition of CeO 2 enhanced the reducibility of the catalysts .…”
Section: Introductionmentioning
confidence: 99%